Analysis of 21st Century Skills of Student on Implementation Project Based Learning and Problem Posing Models in Science Learning (Universitas Negeri Semarang, 2019)
The purpose of this study was to distinguish the analyze the difference 21st-century skills of student between the PjBL and the Problem Posing learning models. This research is a quasi-experimental study. Determination of subjects was performed purposively on fourth-grade students of Randuagung Elementary School as the 1st experimental class, amounting to 35 students, and Sukorejo Elementary School as the 2nd experimental group, amounting to 32 students. Data collection was performed by observing communication and collaboration skills during the learning and providing tests of critical thinking and creativity skills after implementing the models. Data analysis used MANOVA. The results showed that there were significant differences in 21st-century skills between students implemented using the PjBL and the Problem Posing models. The optimal PjBL model implementation is creativity, communication, and collaboration skills, due to the results of the multivariate test are different and have a higher average if compared with the implementation of the Problem Posing model. Whereas the implementation of the Problem Posing model has not been optimal for all skills. Critical thinking skills achieved by a student in both model implementation have no significant difference. The differences in the average of the 21st-century skills gained by the student in the two models do not differ greatly. However, the intensity result is that from four skills on the Problem Posing model, critical thinking skills is improve significantly.